2020
DOI: 10.1101/2020.10.23.353193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mice hypomorphic forPitx3define a minimal dopamine neuron population sufficient for entraining behavior and metabolism to scheduled feeding

Abstract: Pitx3ak mice lack a functioning retina and nearly all dopamine neurons of the substantia nigra (SN). del Rio-Marten et al (2019) reported that entrainment of circadian rhythms to daily light-dark and feeding schedules is absent in these mice. With food limited to 12h/day, food anticipatory circadian rhythms failed to emerge, and metabolic rhythms failed to synchronize with locomotor and feeding rhythms. The authors propose that retinal innervation of the suprachiasmatic nucleus clock is required for developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Importantly, in that study food anticipatory running wheel activity was observed in animals with food available during the light phase. These studies indicate that entrainment of activity and metabolism can be induced by TRF in the absence of caloric restriction, contrary to that stated by Scarpa et al (2022), in agreement with additional studies showing that temporal restriction of feeding to the scotophase in mice without reducing calorie intake reprograms the regulation of energy metabolism to optimize energy balance (Chaix et al, 2019;Hatori et al, 2012;Johnston et al, 2016;Shamsi et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Importantly, in that study food anticipatory running wheel activity was observed in animals with food available during the light phase. These studies indicate that entrainment of activity and metabolism can be induced by TRF in the absence of caloric restriction, contrary to that stated by Scarpa et al (2022), in agreement with additional studies showing that temporal restriction of feeding to the scotophase in mice without reducing calorie intake reprograms the regulation of energy metabolism to optimize energy balance (Chaix et al, 2019;Hatori et al, 2012;Johnston et al, 2016;Shamsi et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…In their Matters Arising article, Scarpa et al (2022) call into question most of the conclusions of our previous study (Del Rı ´o-Martı ´n et al, 2019) on the circadian organization of biological cycles of Pitx3 ak mice, arguing that they were drawn primarily from averaging metabolic activity or molecular data. We disagree with that argument, since data from individual mice were taken into consideration and the analyses from which we drew most of our main conclusions were not based solely on averaging data.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously, we provided evidence that deletion of D1R in mice nearly eliminated behavioral anticipation but not the body temperature increase associated with a daily meal; we proposed that the circuitry sufficient for FAA involved D1R mediated signaling from the SN into the dorsal striatum [ 21 ]. More recently, we demonstrated that mice with hypomorphic mutations in paired-like homeodomain transcription factor 3 , a transcription factor necessary for survival of 95% of SN dopamine neurons, defines a minimal population of dopamine neurons sufficient for FAA and metabolic entertainment to timed feeding [ 47 ]. To further resolve the circuitry of D1R-expressing neurons and their role promoting FAA, we created a conditional knockout of D1R in Vgat-Cre expressing neurons.…”
Section: Discussionmentioning
confidence: 99%